Editorial [Hot Topic: Spondyloarthritis in Asia Guest Editor: Chung-Tei Chou] - Chou, Chung-Tei (Current Rheumatology Reviews, 2008)
Spondyloarthritis (SpA) is a common rheumatic disorder. It consists of ankylosing spondylitis (AS), reactive arthritis (ReA), psoriatic arthritis (PsA), inflammatory bowel disease (IBD), juvenile chronic arthritis (JCA), and undifferentiated spondyloarthritis (USpA), etc. Presenting differences from rheumatoid arthritis, SpA is characterized by axial and sacroiliac joint involvement, anterior uveitis, enthesopathy, dactylitis, positive HLA-B27 and high family tendency. Many studies to explore the prevalence, genetic marker, pathogenesis, clinical features, radiologic image, pathology and management have been largely conducted in the Western countries. By the clinical application of biologic therapy, it becomes more understandable for etiology and pathogenesis in SpA. As a matter of fact, the majority of studies are performed in the Western countries and fewer in Asian countries. Asia has a very large population in the world. Recently, a review of the literature disclosed that Asian investigators have published more and more researches in SpA. In this regard, I invited several authors from different Asian countries to contribute a special issue of ‘Spondyloarthritis in Asia”, and wish it can provide the knowledge and understanding of SpA in Asian people.